2020
DOI: 10.1021/acsomega.0c03377
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Stabilizing Sub-100 nm Mesoporous Silica Nanoparticles for Ultrasound Theranostics

Abstract: Recent studies have demonstrated that gas-stabilizing particles can generate cavitating micron-sized bubbles when exposed to ultrasound, offering excellent application potential, including ultrasound imaging, drug delivery, and tumor ablation. However, the majority of the reported gas-stabilizing particles are relatively large (>200 nm), and smaller particles require high acoustic pressures to promote cavitation. Here, this paper reports the preparation of sub-100 nm gas-stabilizing nanoparticles (GSNs) that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…The MSNs were stabilized by gas that can initiate cavitation at low and high acoustic intensity. They reported that under low acoustic pressure, ultrasound imaging was produced, while at high acoustic pressure, the microbubbles collapsed, which produced shockwaves and ablate the nearby cells or transiently perforate their membranes [ 234 ]. Lee and colleagues reported on multifunctional MSNs as imaging agents and carriers for photothermal therapy of cancer.…”
Section: Multifunctional Drug Delivery Agentmentioning
confidence: 99%
“…The MSNs were stabilized by gas that can initiate cavitation at low and high acoustic intensity. They reported that under low acoustic pressure, ultrasound imaging was produced, while at high acoustic pressure, the microbubbles collapsed, which produced shockwaves and ablate the nearby cells or transiently perforate their membranes [ 234 ]. Lee and colleagues reported on multifunctional MSNs as imaging agents and carriers for photothermal therapy of cancer.…”
Section: Multifunctional Drug Delivery Agentmentioning
confidence: 99%
“…The micron-sized bubbles generated by GSNs can backscatter the ultrasound waves and improve the contrast of ultrasound images [ 34 , 35 , 39 ]. In addition, the violent collapse of these bubbles can induce mechanical effects (e.g., shock waves and water jets) in the tissue, which are useful for improving the outcomes of ultrasound-based therapies such as tumor ablation or localized drug delivery [ 37 , 40 , 46 , 47 ].…”
Section: Gas Stabilizing Nanoparticles (Gsns) As Exogenous Nuclei For Acoustic Cavitationmentioning
confidence: 99%
“…Following these pioneering studies, several GSNs have been developed using different materials, including mesoporous silica, porous silicon, gold, and polymers (Fig. 3 ) [ 34 36 , 39 41 , 44 , 46 49 , 70 , 73 , 78 87 ]. While, as discussed in the previous section, the exact mechanism of cavitation inception by GSNs is yet to be understood, these studies found that a hydrophobic surface or cavity is required to prepare GSNs with high acoustic activity (i.e., cavitation inception at low acoustic intensities).…”
Section: Gas Stabilizing Nanoparticles (Gsns) As Exogenous Nuclei For Acoustic Cavitationmentioning
confidence: 99%
See 2 more Smart Citations